Sulfide-based solid electrolyte having enhanced inter-particle binding power,

By controlling reaction temperature and heat-treating sulfide-based solid electrolytes, the inter-particle bonding force is enhanced, stabilizing the slurry and improving battery performance and safety.

CN119153764APending Publication Date: 2024-12-17HYUNDAI MOTOR CO LTD +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410059001.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-06-16
Filing Date
2024-01-16
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

Sulfide-based solid electrolytes face challenges with weak inter-particle bonding forces leading to unstable slurry formation during battery manufacturing, due to limited grain growth and breakage of fine primary particles, which affects the safety and performance of lithium secondary batteries.

Method used

A sulfide-based solid electrolyte with enhanced inter-particle bonding force is achieved by controlling the reaction temperature during precursor preparation and heat-treating the precursor at specific temperatures to form secondary particles with strong cohesion, resulting in a stable slurry with uniform dispersion.

Benefits of technology

The solution provides a stable and high-quality slurry with reduced particle breakage and improved slurry viscosity stability, enhancing the safety and performance of lithium secondary batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119153764A_ABST
    Figure CN119153764A_ABST
Patent Text Reader

Abstract

The present invention relates to a sulfide-based solid electrolyte having enhanced inter-particle binding force, a slurry having the same, and a method for preparing the same. A sulfide-based solid electrolyte containing secondary particles in which primary particles are agglomerated. By using a sulfide-based solid electrolyte, a uniform, stable, and high-quality slurry in which primary particles have a strong inter-particle binding force can be prepared.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a sulfide-based solid electrolyte comprising secondary particles formed by agglomeration of primary particles. By using the sulfide-based solid electrolyte, a uniform, stable and high-quality slurry can be prepared, wherein the primary particles have a strong inter-particle bonding force. Background Art

[0002] Today, secondary batteries are widely used in large devices such as automobiles and power storage systems, and in small devices such as mobile phones, camcorders, and notebook computers.

[0003] As the applications of rechargeable batteries continue to expand, the demand for improved safety and higher performance is also increasing.

[0004] As a type of secondary battery, lithium secondary batteries have the advantages of high energy density and large capacity per unit area compared with nickel-manganese batteries or nickel-cadmium batteries.

[0005] Most of the electrolytes used in conventional lithium secondary batteries are liquid electrolytes, such as organic solvents. For this reason, safety issues such as electrolyte leakage and the risk of fire due to leakage are of great concern.

[0006] Recently, there has been growing interest in all-solid-state batteries that utilize solid electrolytes instead of liquid electrolytes to improve the safety of lithium secondary batteries.

[0007] Solid electrolytes are not flammable or flame retardant. For this reason, solid electrolytes are safer than liquid electrolytes.

[0008] There are two types of solid electrolytes: oxide-based solid electrolytes and sulfide-based solid electrolytes. Compared with oxide-based solid electrolytes, sulfide-based solid electrolytes have the advantages of high lithium ion conductivity and stability over a wide voltage range.

[0009] Unlike oxide-based solid electrolytes, sulfide-based solid electrolytes have the problem of being unable to undergo crystallization heat treatment at high temperatures due to element volatilization. Therefore, sulfide-based solid electrolytes have the problem of limited grain growth and contain a large number of fine primary particles. Weakly cohesive primary particles are easily broken during battery manufacturing, resulting in unstable slurry.

[0010] The information disclosed in the above Background section is for helping understanding the background of the invention and should not be regarded as an admission that the information constitutes any part of the prior art. Summary of the invention

[0011] Various aspects of the present invention are directed to providing a sulfide-based solid electrolyte made of highly cohesive primary particles and a method for preparing the same.

[0012] The objects of the present invention are not limited to the above objects. The above and other objects of the present invention will become more apparent from the following description and will be achieved by the means and combinations of means described in the claims.

[0013] The sulfide-based solid electrolyte according to an exemplary embodiment of the present invention may include secondary particles formed by agglomeration of primary particles.

[0014] The sulfide-based solid electrolyte may have a primary particle-to-particle bonding force ε of 0.3 min·W·μm / mg or more.

[0015] Sulfide-based solid electrolytes can have a 55 μm -1 or less strain This strain is expressed by the following equation 1.

[0016] [Equation 1]

[0017]

[0018] Here, the particle size i 之前 Can indicate median diameter D50,

[0019] i 之前 The vol% may represent the volume percentage of particles having a median diameter D50 of i μm before ultrasonic treatment.

[0020] Particle size 之后 The median diameter D50 can be expressed.

[0021] i 之后 The vol% may represent the volume percentage of particles having a median diameter D50 of i μm after ultrasonic treatment.

[0022] Initial differential weight of sulfide-based solid electrolytes Can be 40μm -1 or smaller, as expressed by Equation 2 below.

[0023] [Equation 2]

[0024]

[0025] Here, the particle size i 之前 Can indicate median diameter D50,

[0026] i 之前 The vol% may represent the volume percentage of particles having a median diameter D50 of i μm before ultrasonic treatment.

[0027] The slurry according to an exemplary embodiment of the present invention may include a sulfide-based solid electrolyte and a dispersion medium.

[0028] Initial viscosity of the slurry μ 0 It can be 5,000cp or less.

[0029] The long-term change in slurry viscosity may be 10% or less, as expressed by Equation 3 below.

[0030] [Equation 3]

[0031]

[0032] Here, μ 0 It can represent the initial viscosity.

[0033] μ 48h It may refer to the viscosity measured after storage for 48 hours after the initial viscosity is measured.

[0034] According to an exemplary embodiment of the present invention, a method of preparing a sulfide-based solid electrolyte may include: preparing raw materials; obtaining a precursor by reacting the raw materials; and obtaining the sulfide-based solid electrolyte by heat-treating the precursor.

[0035] In the process of obtaining the precursor, the precursor may be obtained by stirring the raw materials to promote the reaction and maintaining the raw materials at a temperature ranging from 0°C to 30°C.

[0036] Obtaining the sulfide-based solid electrolyte may be performed by heat treating the precursor at a temperature ranging from 400°C to 550°C.

[0037] According to the present invention, a sulfide-based solid electrolyte having a high bonding force between primary particles can be obtained, and a method for preparing the electrolyte can be obtained.

[0038] According to the present invention, a stable slurry in which a sulfide-based solid electrolyte is uniformly dispersed can be obtained.

[0039] The effects and advantages of the present invention are not limited to the above-mentioned effects and advantages. The effects and advantages of the present invention should be understood to include all effects and advantages that can be inferred from the following description. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 An all-solid-state battery according to an exemplary embodiment of the present invention is shown;

[0041] Figure 2 A scanning electron microscope (SEM) image of a precursor according to one preparation example of the present invention is shown;

[0042] Figure 3 shows an SEM image of a precursor according to a comparative preparation example;

[0043] Figure 4 shows a SEM image of the sulfide-based solid electrolyte according to Example 1;

[0044] Figure 5 shows a SEM image of the sulfide-based solid electrolyte according to Example 2;

[0045] Figure 6 shows a SEM image of the sulfide-based solid electrolyte according to Example 3;

[0046] Figure 7 shows a SEM image of the sulfide-based solid electrolyte according to Comparative Example 1;

[0047] Figure 8 shows an SEM image of the sulfide-based solid electrolyte according to Comparative Example 2;

[0048] Fig. 9 shows the results of analysis of the particle size distribution of the sulfide-based solid electrolyte according to Example 1, wherein the analysis was performed before and after treatment with an ultrasonic pulverizer;

[0049] Fig.10 shows the results of analysis of the particle size distribution of the sulfide-based solid electrolyte according to Example 2, wherein the analysis was performed before and after treatment with an ultrasonic pulverizer;

[0050] Fig.11 shows the results of analysis of the particle size distribution of the sulfide-based solid electrolyte according to Example 3, wherein the analysis was performed before and after treatment with an ultrasonic pulverizer;

[0051] Fig.12 shows the results of analysis of the particle size distribution of the sulfide-based solid electrolyte according to Comparative Example 1, wherein the analysis was performed before and after treatment with an ultrasonic pulverizer;

[0052] Fig.13 shows the results of analysis of the particle size distribution of the sulfide-based solid electrolyte according to Comparative Example 2, wherein the analysis was performed before and after treatment with an ultrasonic pulverizer;

[0053] Fig.14 The results of stability analysis of a slurry containing a sulfide-based solid electrolyte according to Example 1 are shown, the analysis being performed using a dispersion stabilizer (Turbiscan);

[0054] Fig.15 Show Fig.14 A magnified view of the results from the 4mm to 36mm area;

[0055] Fig.16The results of stability analysis of a slurry including the sulfide-based solid electrolyte according to Example 2 are shown, the analysis being performed using a dispersion stabilizer;

[0056] Fig.17 Show Fig.16 A magnified view of the results from the 4mm to 36mm area;

[0057] Fig.18 shows the results of observing the surface of a film formed by applying a slurry including the sulfide-based solid electrolyte according to Comparative Example 1 to a substrate; and

[0058] Fig.19 The results of observing the surface of a film formed by applying a slurry including the sulfide-based solid electrolyte according to Example 2 to a substrate are shown.

[0059] It is to be understood that the accompanying drawings are not necessarily to scale, and that they show various features that are somewhat simplified to illustrate the basic principles of the invention. The specific design features of the invention as included herein (including, for example, specific size, orientation, location, and shape) will be determined in part by the specific target application and use environment.

[0060] In the figures, reference numbers refer to the same or equivalent parts of the present invention throughout the several figures of the drawing. DETAILED DESCRIPTION

[0061] The above objects, other objects, features and advantages of the present invention will be easily understood by the following exemplary embodiments associated with the accompanying drawings. However, the present invention is not limited to the embodiments described herein and can be implemented in other forms. The embodiments described herein provided make the disclosed content complete and sufficient and can fully convey the spirit of the present invention to those skilled in the art.

[0062] In all the drawings, the same elements are represented by the same reference numerals. In the drawings, for the sake of clarity of the present invention, the size of the structure is larger than the actual size. The terms "first", "second" etc. used in the specification can be used to describe various components, but components should not be interpreted as being limited to these terms. These terms are only used to distinguish one component from another component. For example, without departing from the scope of the present invention, the first component can be referred to as the second component, and the second component can also be referred to as the first component. As used in this article, unless the context clearly indicates otherwise, the singular form "one", "an" and "the / said" are intended to also include plural forms.

[0063] It should be further understood that when used in this specification, the terms "comprise", "include" or "have" specify the presence of the features, regions, wholes, steps, operations, elements and / or components described, but do not exclude the presence or addition of one or more other features, regions, wholes, steps, operations, elements, components and / or combinations thereof. It should also be understood that when an element such as a layer, film, region or sheet is referred to as being "above" another element, it can be directly above the other element, or there can be intermediate elements between them. Similarly, when an element such as a layer, film, region or sheet is referred to as being "below" another element, it can be directly below the other element, or there can be intermediate elements between them.

[0064] Unless otherwise stated, all numbers, values ​​and / or expressions used in this article to express the amount of components, reaction conditions, polymer compositions and mixtures should be considered as approximate values ​​containing various uncertainties (especially inherent in obtaining these values, which will affect the measured values), and should therefore be understood to be modified by the term "about" in all cases. In addition, when a numerical range is disclosed in this specification, the range is continuous and includes all values ​​from the minimum value to the maximum value of the range, unless otherwise stated. In addition, when such a range involves integer values, all integers including the minimum value to the maximum value are included unless otherwise stated.

[0065] Figure 1 An all-solid-state battery according to an exemplary embodiment of the present invention is shown. The all-solid-state battery may include a cathode 10, an anode 20, and a solid electrolyte layer 30 interposed between the cathode 10 and the anode 20. At least one of the cathode 10, the anode 20, and the solid electrolyte layer 30 may include a sulfide-based solid electrolyte according to an exemplary embodiment of the present invention.

[0066] The sulfide-based solid electrolyte may be a compound including elemental lithium (Li), elemental phosphorus (P), elemental sulfur (S), etc. For example, the sulfide-based solid electrolyte may include Li 3 PS 4 .

[0067] However, the composition of the sulfide-based solid electrolyte is not limited thereto. The sulfide-based solid electrolyte may include a compound represented by Formula 1 shown below or a compound represented by Formula 2 shown below.

[0068] [Formula 1]

[0069] Li 7 -aPS 6 -aX a

[0070] Here, a satisfies the condition of 1≤a≤2.

[0071] Here, X represents a halogen element.

[0072] [Formula 2]

[0073] Li 7 -aPS 6 -a(X1 b X2 1-b ) a

[0074] Here, a satisfies the condition of 1 ≤ a ≤ 2.

[0075] Here, b satisfies the condition of 0 < b < 1.

[0076] X1 and X2 can be different halogen elements.

[0077] The sulfide-based solid electrolyte may further include an element selected from boron (B), carbon (C), nitrogen (N), aluminum (Al), silicon (Si), vanadium (V), manganese (Mn), iron (Fe), cobalt (Co), nickel (Ni), copper (Cu), zinc (Zn), gallium (Ga), germanium (Ge), arsenic (As), silver (Ag), cadmium (Cd), tin (Sn), antimony (Sb), tellurium (Te), lead (Pb), bismuth (Bi), and combinations thereof. The selected element may be included to replace phosphorus (P) or sulfur (S).

[0078] The sulfide-based solid electrolyte may have a thio-LISICON crystal structure.

[0079] The sulfide-based solid electrolyte may include secondary particles formed by agglomeration of primary particles. The sulfide-based solid electrolyte according to an exemplary embodiment of the present invention has a high binding force between primary particles, such that particle growth is sufficient and the particles do not break when included in a slurry phase. The binding force between primary particles can be increased by adjusting raw material reaction conditions or heat treatment conditions during the preparation of the sulfide-based solid electrolyte.

[0080] According to an exemplary embodiment of the present invention, a method for preparing a sulfide-based solid electrolyte may include the following steps: preparing raw materials; obtaining a precursor by reacting the raw materials; and obtaining the sulfide-based solid electrolyte by heat-treating the precursor.

[0081] The raw materials can be prepared by weighing appropriate amounts of required materials according to the composition of the desired sulfide-based solid electrolyte. For example, the raw materials may include a lithium source, a sulfide source, a halogen source, etc.

[0082] Examples of the lithium source may include Li 2 S, lithium metal, etc.

[0083] Examples of the sulfide source may include P 2 S3 , P 2 S 5 , P 4 S 3 , P 4 S 5 , P 4 S 7 , P 4 S 10 , elemental sulfur, etc.

[0084] Examples of the halogen source may include LiX (X=F, Cl, Br, or I) and simple halogens.

[0085] As used herein, the term "element" refers to a substance composed of a single element and exhibiting unique chemical properties. Therefore, lithium element refers to a substance composed only of lithium and exhibiting unique chemical properties, and sulfur element refers to a substance composed only of sulfur and exhibiting unique chemical properties.

[0086] The raw material prepared as described above is added to the solvent and stirred to cause a reaction. As a result, a precursor can be obtained.

[0087] The solvent is not particularly limited, but any solvent capable of dissolving the raw material can be used without limitation. For example, the solvent may include at least one selected from methanol, ethanol, propanol, butanol, dimethyl carbonate, ethyl acetate, tetrahydrofuran, 1,2-dimethoxyethane, propylene glycol dimethyl ether, acetonitrile and combinations thereof.

[0088] When the raw materials are introduced into the solvent and then stirred, the raw materials are dissolved in the solvent, and the raw materials react with each other to produce the precursor. The stirring conditions are not particularly limited, and the stirring is carried out under the conditions of a predetermined stirring speed and reaction time that enable the raw materials to fully dissolve in the solvent and react with each other.

[0089] However, the temperature of the raw materials must be controlled during the reaction because the natural increase in temperature caused by the heat of reaction of the raw materials over-accelerates the rate of formation of primary particles, resulting in uneven particles. Specifically, the present invention is characterized in that the raw materials are reacted under stirring while the temperature of the raw materials is maintained in the range of 0°C to 30°C to obtain a precursor. When the temperature of the raw materials exceeds 30°C, primary particles may be formed at an excessively high rate and their sizes may be uneven. When the temperature of the raw materials is below 0°C, the reaction between the raw materials may not occur normally.

[0090] The method for maintaining the temperature of the raw materials is not particularly limited. For example, the temperature of the raw materials can be maintained by placing the reactor containing the raw materials in a bath for reaction.

[0091] The method may further comprise the step of drying the precursor. The drying step is performed to remove the solvent.

[0092] The step of drying can be performed under conditions where the precursor does not deteriorate. For example, the precursor can be vacuum dried at a temperature in the range of 25° C. to 200° C. for a duration in the range of 2 hours to 20 hours. According to an exemplary embodiment of the present invention, vacuum drying is performed to prevent the precursor from reacting with external moisture or the like.

[0093] The precursor may then be heat treated to obtain a crystallized sulfide-based solid electrolyte. The sulfide-based solid electrolyte may include secondary particles formed by agglomeration of primary particles formed by the above reaction. The heat treatment may be performed at a temperature in the range of 400°C to 550°C for a duration in the range of 1 hour to 10 hours. When the temperature of the heat treatment is within the above range, the inter-particle bonding force of the primary particles increases, which can prevent the sulfide-based solid electrolyte from fragmenting during slurry preparation.

[0094] The method may further include the step of grinding the sulfide-based solid electrolyte obtained as described above to a desired particle size.

[0095] The sulfide-based solid electrolyte obtained as described above is introduced into a dispersion medium alone or in combination with other components such as active materials, binders, conductors, etc. to prepare a slurry. The slurry may be applied to a substrate to form the cathode 10 , the anode 20 , and / or the solid electrolyte layer 30 .

[0096] The dispersion medium is not particularly limited. Any material that can well disperse the sulfide-based solid electrolyte, active material, etc. without reacting with it will be used as the dispersion medium. For example, the dispersion medium may include at least one selected from toluene, heptane, N-methyl-2-pyrrolidone (NMP), acetone, N,N-dimethylformamide (DMF) and a combination thereof.

[0097] Other forms of the present invention will be described in more detail by the following examples. The following examples are only used to help understand the present invention and are not intended to limit the scope of the present invention.

[0098] Preparation Example

[0099] Preparation includes Li 2 S.P. 2 S 5 and LiCl raw materials to meet the requirements of Li 6 PS 5 The raw materials are added to the solvent and stirred to cause a reaction, thereby preparing a precursor. The temperature of the raw materials is controlled using a cooling device so that the temperature of the raw materials during the reaction is within a range of 0° C. to 30° C. Figure 2A scanning electron microscope (SEM) image of a precursor prepared according to Preparation Example is shown.

[0100] Comparative Preparation Examples

[0101] The precursor was prepared using the same raw materials and methods as in the above examples, except that the temperature of the raw materials was not controlled during the reaction. In the reaction of the comparative preparation example, the temperature of the raw materials was about 30°C to 50°C. Figure 3 Shown is an SEM image of a precursor according to Comparative Preparation Example.

[0102] refer to Figure 3 In the precursor according to the comparative preparation example, there are a large number of extremely fine primary particles with a size of tens to hundreds of nanometers. Figure 2 , it can be seen that the precursor according to the preparation example has relatively large primary particles. The presence of small primary particles with a size of tens to hundreds of nanometers is relatively small. When preparing the precursor, the temperature rises due to the exothermic reaction of the raw materials, and the particles begin to grow. In this case, too much reaction heat can cause the particles to grow rapidly and unevenly. Therefore, the present invention prevents the rapid and uneven growth of primary particles by keeping the temperature of the raw materials at a lower temperature during the reaction.

[0103] Example 1

[0104] The precursor prepared according to Preparation Example was heat-treated at about 430° C., thereby preparing a sulfide-based solid electrolyte.

[0105] Example 2

[0106] The precursor prepared according to Preparation Example was heat-treated at about 500° C., thereby preparing a sulfide-based solid electrolyte.

[0107] Example 3

[0108] The precursor prepared according to Preparation Example was heat-treated at about 550° C., thereby preparing a sulfide-based solid electrolyte.

[0109] Comparative Example 1

[0110] The precursor prepared according to Comparative Preparation Example was heat-treated at about 430° C., thereby preparing a sulfide-based solid electrolyte.

[0111] Comparative Example 2

[0112] The precursor prepared according to Comparative Preparation Example was heat-treated at about 500° C., thereby preparing a sulfide-based solid electrolyte.

[0113] Figure 4A SEM image of the sulfide-based solid electrolyte according to Example 1 is shown. Figure 5 An SEM image of the sulfide-based solid electrolyte according to Example 2 is shown. Figure 6 An SEM image of the sulfide-based solid electrolyte according to Example 3 is shown. Figure 7 A SEM image of the sulfide-based solid electrolyte according to Comparative Example 1 is shown. Figure 8 A SEM image of the sulfide-based solid electrolyte according to Comparative Example 2 is shown.

[0114] refer to Figure 7 The sulfide-based solid electrolyte according to the comparative example has secondary particles formed by weak aggregation of primary particles of tens to hundreds of nanometers, as evidenced by the large number of gaps between the primary particles and the large number of voids within each secondary particle.

[0115] refer to Figures 4 to 6 , the sulfide-based solid electrolyte according to any one of Examples 1 to 3 has a high bonding force between primary particles, as evidenced by the small gaps between primary particles and the absence of voids in secondary particles.

[0116] Strain of each sulfide-based solid electrolyte according to Examples 1 to 3 and Comparative Examples 1 to 2 The interparticle bonding force ε of the primary particles was evaluated by particle size distribution (PSD) analysis. Specifically, the particle size distribution of each sulfide-based solid electrolyte was measured before and after treatment with a probe-type ultrasonic pulverizer. The power of the probe was about 200 W, and a small amount of sulfide-based solid electrolyte was subjected to strengthening treatment for about 60 seconds.

[0117] Strain in sulfide-based solid electrolytes It can be the differential weight before and after treatment with ultrasonic pulverizer Changes in differential weight It is the value obtained by dividing the volume percentage of particles having a predetermined particle size by the median diameter D50 of the particles. The differential weight indicates the change in the effect of particle size. It can be shown that as the particle size decreases, the particle size has an increasing influence on the quality of the slurry or film. It can be expressed by the following equation.

[0118]

[0119] Particle size 之前 Indicates the median diameter D50 of the particles, i 之前 The vol% represents the volume percentage of particles having a median diameter D50 of i μm before ultrasonic treatment.

[0120] Particle size之后 Indicates the median diameter D50 of the particles, i 之后 The vol% represents the volume percentage of particles having a median diameter D50 of i μm after ultrasonic treatment.

[0121] In this equation, the total weight can be set by integrating the submicron value (ie, less than or equal to 1 μm) which has a major influence on the quality of the slurry or film.

[0122] Initial differential weight It can express the initial differential weight of the particles before they are treated with an ultrasonic pulverizer. It can be expressed by the following equation.

[0123]

[0124] Particle size 之前 Indicates the median diameter D50 of the particles, i 之前 The vol% represents the volume percentage of particles having a median diameter D50 of i μm before ultrasonic treatment.

[0125] The interparticle bonding force ε of primary particles is an interparticle factor of primary particles forming secondary particles and can reflect the relative energy applied when the sulfide-based solid electrolyte is treated with an ultrasonic pulverizer. The interparticle bonding force ε of primary particles can be expressed by the following equation.

[0126]

[0127] Here, t represents the treatment time of the ultrasonic pulverizer. Here, p represents the power of the probe. W represents the weight of the sulfide-based solid electrolyte treated with the ultrasonic pulverizer. Represents the strain of the sulfide-based solid electrolyte.

[0128] Fig. 9 The analysis results of the particle size distribution of the sulfide-based solid electrolyte according to Example 1 are shown, wherein the analysis was performed before and after treatment with an ultrasonic pulverizer. Fig.10 The analysis results of the particle size distribution of the sulfide-based solid electrolyte according to Example 2 are shown, wherein the analysis was performed before and after treatment with an ultrasonic pulverizer. Fig.11 The analysis results of the particle size distribution of the sulfide-based solid electrolyte according to Example 3 are shown, wherein the analysis was performed before and after treatment with an ultrasonic pulverizer. Fig.12 The analysis results of the particle size distribution of the sulfide-based solid electrolyte according to Comparative Example 1 are shown, wherein the analysis was performed before and after treatment with an ultrasonic pulverizer. Fig.13The results of analysis of the particle size distribution of the sulfide-based solid electrolyte according to Comparative Example 2 are shown, wherein the analysis was performed before and after treatment with an ultrasonic pulverizer. Figures 9 to 13 The strain of each sulfide-based solid electrolyte is calculated based on the results of Initial differential weight and the inter-particle bonding force ε of the primary particles are shown in Table 1 below.

[0129] [Table 1]

[0130]

[0131]

[0132] Referring to Table 1, in the sulfide-based solid electrolyte according to an exemplary embodiment of the present invention, the interparticle binding force ε of the primary particles is greater than or equal to 0.3 min·W·μm / mg. The upper limit of the interparticle binding force ε of the primary particles is not particularly limited. It may be less than or equal to 2 min·W·μm / mg.

[0133] The sulfide-based solid electrolyte according to an exemplary embodiment of the present invention has a thickness of 55 μm. -1 or less strain strain There is no particular lower limit. For example, it is greater than or equal to 10 μm. -1 .

[0134] Initial differential weight of the sulfide-based solid electrolyte according to an exemplary embodiment of the present invention Less than or equal to 40μm -1 Initial differential weight There is no particular lower limit. For example, it is greater than or equal to 1 μm -1 .

[0135] Referring to Table 1, the sulfide-based solid electrolyte according to Comparative Example 1 has the lowest inter-particle bonding force ε of the primary particles, and the sulfide-based solid electrolyte according to Example 2 has the highest inter-particle bonding force ε of the primary particles. In addition, in the case of Comparative Example 2, the inter-particle bonding force ε of the primary particles is relatively strong, but the initial differential weight is 2.34 W / m / s, which is 0.04 W / m / s, compared with the examples. Therefore, when a slurry was prepared from the electrolyte of Comparative Example 2, the slurry had a high initial viscosity and a high secular change in viscosity, thereby forming a low-quality film.

[0136] Each sulfide-based solid electrolyte according to Examples 1 to 3 and Comparative Examples 1 and 2 was dispersed in a dispersion medium to prepare a slurry. The initial viscosity of each slurry was measured, and the long-term change in the viscosity of each slurry was calculated by measuring the viscosity of each slurry after storing for 48 hours after measuring the initial viscosity. The results are shown in Table 2 below.

[0137] [Table 2]

[0138] category Initial viscosity [cp] Viscosity after 48 hours [cp] Long-term change [%] Comparative Example 1 6,240 7,340 17.63 Comparative Example 2 6,560 7,520 14.6 Example 1 4,760 5,100 7.1 Example 2 4,580 4,640 1.3 Example 3 4,380 4,560 4.1

[0139] Referring to Table 2, the initial viscosity μ of the slurry including the sulfide-based solid electrolyte according to an exemplary embodiment of the present invention is 0 Here, the initial viscosity μ 0 It can refer to the viscosity measured when the sulfide solid electrolyte is added to the dispersion medium and stirred for a sufficient time so that the sulfide solid electrolyte is uniformly dispersed in the dispersion medium. Initial viscosity μ 0 The lower limit is not particularly limited. For example, the lower limit is greater than or equal to 3,000 cp.

[0140] In addition, the long-term change in viscosity of the slurry containing the sulfide-based solid electrolyte according to an exemplary embodiment of the present invention is 10% or less, as expressed by the following equation. The lower limit of the long-term change is not particularly limited. For example, the lower limit is greater than or equal to 1%.

[0141]

[0142] μ 0 represents the initial viscosity, and μ 48h It indicates the viscosity measured after storage for 48 hours after the initial viscosity is measured.

[0143] Referring to Table 2, the slurries containing the respective sulfide-based solid electrolytes according to Examples 1 and 2 are highly unstable because they have high initial viscosity and high long-term changes in viscosity. On the other hand, it can be seen that the slurry of Example 2 is quite stable, with a long-term change in viscosity of about 1%.

[0144] Fig.14 The results of stability analysis of a slurry including the sulfide-based solid electrolyte according to Example 1 are shown, the analysis being performed using a dispersion stabilizer (Turbiscan). Fig.15 Show Fig.14 A magnified view of the results from the 4mm to 36mm area.

[0145] Fig.16 The results of stability analysis of a slurry including the sulfide-based solid electrolyte according to Example 2 are shown, the analysis being performed using a dispersion stabilizer. Fig.17 Show Fig.16 A magnified view of the results from the 4mm to 36mm area.

[0146] The Turbiscan is an optical analyzer that uses the intensity of the light transmitted after being emitted from the light source and the intensity of the scattered light to analyze the physical and chemical properties of the sample. Each slurry was injected into a 70 mm high cylindrical glass bottle until the height was about 42 mm, and allowed to stand for about 48 hours before being mounted on the Turbiscan. The light source was operated so that the glass bottle was irradiated with light of a near-infrared wavelength (λ=880 nm) at intervals of about 40 μm along the height direction of the glass bottle. The intensity of the transmitted light and the scattered light was measured using a transmittance meter located opposite the light source and a backscatter meter located at a 45° angle to the light source.

[0147] refer to Fig.14 , the slurry containing the sulfide-based solid electrolyte according to Comparative Example 1 experienced significant flocculation and settling of particles on the vial over time. In addition, given the asymmetry of the variation values ​​at the top near 40 mm height and the bottom near 0 mm height, the slurry is expected to exhibit non-ideal, unpredictable variations. Fig.15 , the slurry in the middle region showed large changes and formed a double layer, which means that the slurry is highly unstable.

[0148] refer to Fig.16 , the slurry containing the sulfide-based solid electrolyte according to Example 2 showed about 85% reduction in flocculation and sedimentation of particles compared to the slurry containing the sulfide-based solid electrolyte according to Comparative Example 1. In addition, unlike Comparative Example 1, the slurry is expected to show simple, predictable changes given the symmetry of the change values ​​near 40 mm at the top and near 0 mm at the bottom. Fig.17 , it can be seen that Fig.15 In contrast, the slurry is extremely stable, with relatively low variations in the middle region.

[0149] Fig.18 The results of observing the surface of a film formed by applying a slurry including the sulfide-based solid electrolyte according to Comparative Example 1 to a substrate are shown. Fig.19 The results of observing the surface of a film formed by applying a slurry including the sulfide-based solid electrolyte according to Example 2 to a substrate are shown.

[0150] refer to Fig.18 and Fig.19 , the surface of each membrane made of the slurry including the sulfide-based solid electrolyte according to Example 2 had a uniform appearance quality, and the surface did not have any unevenness, pinholes, and the like.

[0151] Although examples and experimental examples according to various exemplary embodiments of the present invention have been disclosed for illustrative purposes, those skilled in the art will appreciate that various modifications, additions and substitutions are possible, without departing from the scope and spirit of the invention as defined in the accompanying claims.

Claims

1. A sulfide-based solid electrolyte comprising: Secondary particles formed by the aggregation of primary particles. in, The inter-particle binding force ε of the primary particles is greater than or equal to 0.3 min·W·μm / mg.

2. The sulfide-based solid electrolyte according to claim 1, in, The strain expressed by the following equation 1 Less than or equal to 55μm -1 , [Equation 1] Among them, the particle size i 之前 Indicates the median diameter D50, i 之前 The vol% represents the volume percentage of particles with a median diameter D50 of i μm before ultrasonic treatment, and Particle size 之后 represents the median diameter D50, and i 之后 The vol% represents the volume percentage of particles having a median diameter D50 of i μm after ultrasonic treatment.

3. The sulfide-based solid electrolyte according to claim 1, in, Initial differential weight Less than or equal to 40μm -1 , [Equation 2] Among them, the particle size i 之前 represents the median diameter D50, and i 之前 The vol% represents the volume percentage of particles having a median diameter D50 of i μm before ultrasonic treatment.

4. A slurry comprising a sulfide-based solid electrolyte and a dispersion medium, in, The sulfide-based solid electrolyte comprises secondary particles formed by agglomeration of primary particles, and The inter-particle binding force of the primary particles is greater than or equal to 0.3 min·W·μm / mg.

5. The slurry according to claim 4, in, The strain expressed by the following equation 1 Less than or equal to 55μm -1 , [Equation 1] Among them, the particle size i 之前 represents the median diameter D50, and i 之前 The vol% represents the volume percentage of particles with a median diameter D50 of i μm before ultrasonic treatment. Particle size 之后 represents the median diameter D50, and i 之后 The vol% represents the volume percentage of particles having a median diameter D50 of i μm after ultrasonic treatment.

6. The slurry according to claim 4, in, Initial differential weight Less than or equal to 40μm -1 , [Equation 2] Among them, the particle size i 之前 represents the median diameter D50, and i 之前 The vol% represents the volume percentage of particles having a median diameter D50 of i μm before ultrasonic treatment.

7. The slurry according to claim 4, in, The initial viscosity of the slurry μ 0 5,000cp or less.

8. The slurry according to claim 4, in, The long-term change in the viscosity of the slurry is 10% or less, as expressed by the following equation 3, [Equation 3] Among them, μ 0 represents the initial viscosity, and μ 48h It indicates the viscosity measured after storage for 48 hours after the initial viscosity is measured.

9. A method for preparing a sulfide-based solid electrolyte, the method include: Prepare raw materials; Obtaining a precursor by causing a reaction of a raw material; and The sulfide-based solid electrolyte is obtained by heat treating the precursor, The sulfide-based solid electrolyte comprises secondary particles formed by aggregation of primary particles, and The inter-particle binding force of the primary particles is greater than or equal to 0.3 min·W·μm / mg.

10. The method according to claim 9, in, In the process of obtaining the precursor, the raw materials are reacted under stirring while the temperature of the raw materials is maintained in the range of 0°C to 30°C.

11. The method according to claim 9, in, In the process of obtaining the sulfide-based solid electrolyte, the precursor is heat-treated at a temperature ranging from 400°C to 550°C.

12. The method according to claim 9, in, The strain of the sulfide-based solid electrolyte 55μm -1 or smaller, as expressed by the following equation 1, [Equation 1] Among them, the particle size i 之前 represents the median diameter D50, and i 之前 The vol% represents the volume percentage of particles with a median diameter D50 of i μm before ultrasonic treatment. Particle size 之后 represents the median diameter D50, and i 之后 The vol% represents the volume percentage of particles having a median diameter D50 of i μm after ultrasonic treatment.

13. The method according to claim 9, in, The initial differential weight of the sulfide-based solid electrolyte 40μm -1 or smaller, as expressed by the following equation 2, [Equation 2] Among them, the particle size i 之前 represents the median diameter D50, and i 之前 The vol% represents the volume percentage of particles with a median diameter D50 of i μm before ultrasonic treatment.